Social Security : The Story of British Social Progress and the Beveridge Plan - Great Britain. Inter-departmental Committee on Social Insurance and Allied Services; Davison, Ronald C. (Ronald Conway), 1884- (London : G.G. Harrap and Co., 1943)
1943 1943 1940s 3 preliminary leaves, 9-62 pages : illustrations, diagrams Societies (chiefly insurance companies) should be dropped in favour of direct administration by the new Ministry. No one can doubt that this all-in unification under a Ministry of Social Security would be simpler, more efficient, and, in the long run, more economical to the State. All payments such as children's allowances, retirement pensions, and death benefits would be made through the local Security Offices. The new scheme of assistance or relief on proof of need might also be administered there. Whether the issue of future cash benefits during sickness should also be taken in is open to serious question. Ideally they should not ; for there is a real advantage in associating sick pay with the treatment of sickness and the service of sick visiting. The family doctors of the future should work from the local Health Centre. Domiciliary treatment will radiate out from there to all sick persons who are not sent to hospital. It seems to follow that sickness benefits should also come from the local Health Centre, even though the ultimate responsibility for the unified social insurances is to be in the hands of the Ministry of Social Security. Still less should the payment of unemployment benefit be separated from the agency which tests a man's unemployment claim and tries to find him a suitable job. That agency is the local Employment Exchange, and our whole national network of Employment Exchanges must certainly remain under the Ministry of Labour. Here again the function of making the actual benefit payment must be delegated by the Ministry of Social Security. (b) The Costs of Social Security (see Charts 13 to 16). To make financial estimates of the costs of our improved social services after the war is a precarious and speculative business. In the appendix to the Beveridge Report the Government Actuary had to take the plunge, but, in the opinion of the writer of this book, his task was well-nigh 51 15X/2/566/303